Comparação do método discreto da NBR 6123 e do método do vento sintético para edificações em concreto armado de múltiplos pavimentos - Santos, Vagner Henrique dos (2017)
The economic scenario and the interpersonal relations make the human being focus on large cities and urban planning is necessary in order to concentrate the population in specific regions so as to facilitate their attendance, such as commerce, sanitation, security and public transportation, guaranteeing an ideal logistics for the population. The regions close to these points of service undergo a real estate valuation, becoming more and more common the verticalization of the buildings, in such a way to maximize the constructive potential of the central areas and to minimize the cost of the urban spaces. Therefore, research engineers face the challenge of developing computing techniques and computational modeling to minimize and further approximate the computation of structures to actual requests, reducing material consumption. One of the factors to be considered for designing a structure is the force of the winds upcoming on its surface, contributing to a high consumption of materials, so that the structural parts can withstand the demands of imposed forces. Thus, the objective of this dissertation is to compare the Model of the Discrete Method NBR 6123 (ABNT, 1988) and the Synthetic Wind Method (Franco, 1993) for multiple pavements in reinforced concrete. Two buildings were studied for the two methods, the model I being a tower consisting of 34 floors, with a total height of 103 meters. In the case of Model II, the building consists of 28 floors, with a total height of 65 meters and the asymmetry of the building's porticos causes the deformations to be different, even with similar drag coefficients for the two directions.